Knowledge mapping of mitochondrial calcium uniporter from 2011 to 2022: A bibliometric analysis - Pan, Deng; Xu, Lin; Shi, Dazhuo; Guo, Ming (Frontiers in Physiology, 2023)
Background: Calcium uptake research has a long history. However, the mitochondrial calcium uniporter (MCU) protein was first discovered in 2011. As investigations of MCU represent a new research hotspot, a comprehensive and objective perspective of the field is lacking. Hence, this bibliometric analysis aimed to provide the current study status and trends related to MCU research in the past decade. Methods: Articles were acquired from the Web of Science Core Collection database. We quantified and visualized information regarding annual publications, journals, cocited journals, countries/regions, institutions, authors, and cocited authors by using CiteSpace 5.8.R3 and VOSviewer. In addition, we analysed the citation and keyword bursts related to MCU studies. Results: From 2011 to 2022, 1030 articles were published by 5050 authors from 1145 affiliations and 62 countries or regions. The country with the most published articles was the USA. The institution with the most published articles was the University of Padua. Rosario Rizutto published the most articles and was also the most cocited author. Cell Calcium published the largest number of articles, whereas Journal of Biological Chemistry had the most cocitations. The top 5 keywords related to pathological processes were Ca2+ uptake, oxidative stress, cell death, apoptosis, and oxidative phosphorylation. Calcium uniporter, permeability transition pore, MICU1, ryanodine receptor, and ATP synthase were the top 5 keywords related to molecules. Conclusion: MCU research has grown stably over the last decade. Current studies focus on the structure of the MCU complex and its regulatory effect on mitochondrial calcium homeostasis. In addition, the potential role of MCU in different diseases has been explored. Current studies mostly involve investigations of cancer and neurodegenerative diseases. Our analysis provides guidance and new insights into further MCU research.